Peran Guru PPKn Dalam Mengatasi Terjadinya Perilaku Bullying Pada Siswa Di SMP Negeri 1 Sukamulia - M. Tapaul Jahidin; M. Mabrur Haslan; Sawaludin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to examine the role of Pancasila and Civic Education teachers in addressing bullying behavior among students at SMP Negeri 1 Sukamulia, as well as to identify the supporting and inhibiting factors that influence this role. The background of this study is based on the increasing incidence of bullying in schools, which has a negative impact on students’ social, emotional, and moral development. This research employed a qualitative approach with a descriptive research design. Data were collected through interviews, observations, and documentation. Interviews and observations were conducted with PPKn teachers, guidance and counseling teachers, the school principal, and students. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. The results of the study indicate that PPKn teachers play roles as educators, leaders, motivators, and facilitators. The supporting factors for PPKn teachers in addressing bullying behavior among students at SMP Negeri 1 Sukamulia consist of internal factors, including pedagogical competence, personality, interest, and enthusiasm of PPKn teachers, and external factors, such as family support, extracurricular activities, school policies, and government programs, including Child-Friendly Schools and the Strengthening Character Education program. Meanwhile, the inhibiting factors faced by PPKn teachers in addressing bullying behavior at SMP Negeri 1 Sukamulia include family factors, peer association factors, and students’ lack of discipline and resistance to school rules.